Determining the position and state of post-impact motion of a motor vehicle struck on its side at a road intersection, based on experimental tests - Gidlewski, Mirosław; Prochowski, Leon; Wach, Wojciech (Transport, 2019)
The modelling, simulation, and reconstruction of road accidents are difficult processes, where experimental test results must be used at different stages of the work. Such data are needed e.g. to create or improve models of vehicle collision dynamics and to validate the results of computer simulations of vehicle motion during and after the collision. Within the work, experimental tests were carried out and the test results were utilized for determining specific values of the parameters that characterize the state of motion of the impacted vehicle during the collision and after the vehicle separation from each other. The test results make it possible to determine the initial values to be used in calculations of further free motion of the vehicle after a side impact. In particular, they enable defining the influence of the location of the point of impact against the vehicle side on the position and angle of rotation of the vehicle in relation to the global reference frame and on the value, direction, and sense of the vector of linear velocity of the centre of vehicle mass and the vector of angular velocity of the vehicle body around the vertical axis. These data constitute information sufficient to determine the energy of translation and rotation of the vehicle struck on its side at a road intersection and to carry out a simulation of the vehicle motion immediately following the collision.